Pengaruh Personaliti dan Kepimpinan Terhadap Keberkesanan Pasukan PTD Gred M41 - Wan Khairi, Wan Hamat (2013)
Civil Service in Malaysia has undergone a change due to emphasize elements in each performance and the effectiveness of policy implementation as well as issued. Every great success is the result of the contribution of small units that work well through the spirit and teamwork shown in each assignment. Examining the importance of teams in each achievements, this study has taken steps to examine the effectiveness of the team in the Administrative and Diplomatic Officer (PTD), which is common services Civil Service officer who manages the affairs management in the Ministry/Department/Unit in the production of services whether competitive locally and globally. This finding suggests that two main factors have been studied personality factor and leadership factor provide a significant value towards team effectiveness of PTD Grade M41 through Correlation and Regression Testing. Accordingly, some suggestions are made in this study to help improve the effectiveness of PTD Grade M41 towards achieving world class public services